Adsorption of nickel ions from aqueous solution by exhausted coffee grounds - Sidek, Nurul Haiza (2011)
The possible use of exhausted coffee grounds as an adsorbent for the removal of nickel (II) ions from aqueous solution was investigated as a potential low-cost an alternative treatment to treat wastewater containing nickel (II) and other heavy metal ions. The effects of relevant parameters including contact time, initial concentration and particle size on nickel(II) adsorption were examined. This experiment was conducted at room temperature and no pH adjustment was made prior to the analysis. Batch adsorption studies also revealed that the amount of nickel (II) ions adsorbed per gram weight of exhausted coffee grounds increased with an increased in initial Ni (II) ions concentration with 75.10 to 98.17% of nickel ions removed. The effect of particle size of the exhausted coffee grounds varied for different initial nickel(II) ions concentration studied. Kinetic studies and adsorption isotherm were performed to investigate the mechanism of adsorption of nickel (II) ions. Adsorption data indicated that the adsorption of nickel(II) ions by exhausted coffee grounds was best described by pseudo-second-order kinetic model and Freundlich isotherm model. The exhausted coffee ground from Arabica origin with particle size of 420 - 212μm exhibited a better adsorption than other origin and particle size with a percentage of 96.00 to 98.00% of nickel(II) ions removal for all initial ion concentration tested.